Preparation and electrochemical properties of Li6La3Zr0.7Ti0.3Ta0.5Sb0.5O12 high-entropy Li-garnet solid electrolyte - Ye, Ruijie; Ting, Yin-Ying; Dashjav, Enkhtsetseg; Ma, Qianli; Taminato, Sou; Mori, Daisuke; Imanishi, Nobuyuki; Kowalski, Piotr M.; Eikerling, Michael H.; Kaghazchi, Payam; Finsterbusch, Martin; Guillon, Olivier (Frontiers in Energy Research, 2024)
Garnet-type solid electrolytes stand out as promising Li-ion conductors for the next-generation batteries. It has been demonstrated that the inherent properties of garnets can be tailored by introducing various dopants into their crystal structures. Recently, there has been a growing interest in the concept of high entropy stabilization for materials design. In this study, we synthesized high-entropy garnets denoted as Li6La3Zr0.7Ti0.3Ta0.5Sb0.5O12 (LLZTTSO), wherein Ti, Sb, and Ta occupy the Zr site. The formation of the cubic garnet phase in LLZTTSO was confirmed through X-ray diffraction (XRD), and the resulting lattice parameter agreed with predictions made using computational methods. Despite the substantial porosity (relative density 80.6%) attributed to the low sintering temperature, LLZTTSO exhibits a bulk ionic conductivity of 0.099 mS cm−1 at 25°C, and a total ionic conductivity of 0.088 mS cm−1, accompanied by an activation energy of 0.497 eV. Furthermore, LLZTTSO demonstrates a critical current density of 0.275 mA cm−2 at 25°C, showcasing its potential even without any interfacial modification.